Comparative proteomic analysis of maternal peripheral plasma and umbilical venous plasma from normal and gestational diabetes mellitus pregnancies - Liao, Yun (Medicine (Baltimore), 2018)
Gestational diabetes mellitus (GDM) increases many health risks in offspring. The study aims to investigate the underlying mechanism in fetal risk of GDM. We collected maternal peripheral plasma and umbilical venous plasma samples from 4 GDM and 4 control patients during their delivery at a university-based women's hospital. An isobaric tag for relative and absolute quantitation-labeled proteomics analysis was performed. The enzyme-linked immunosorbent assay was used to confirm the change of cholesteryl ester transfer protein (CETP). Bioinformatic analysis was performed with Ingenuity Pathway Analysis (IPA) software package. We identified 19 up-regulated proteins and 15 down-regulated proteins in GDM peripheral plasma, 29 up-regulated proteins and 69 down-regulated proteins in GDM umbilical venous plasma. CETP concentration was significantly lower in both GDM peripheral plasma and umbilical venous plasma. Upstream regulator analysis predicted follicle-stimulating hormone (FSH) as the activated regulator of differentially expressed proteins. The protein profiles in both GDM peripheral plasma and umbilical venous plasma between normal and GDM patients were significantly different. The results indicated that CETP and FSH might associates with health problem of GDM offspring.